Antagonistic effect of zinc oxide nanoparticle and surfactant on anaerobic digestion: Focusing on the microbial community changes and interactive mechanism. (February 2020) - Zhu, Kongyun; Zhang, Lei; Mu, Lan; Ma, Jiao; Wang, Xuexue; Li, Changjing; Cui, Yubo; Li, Aimin
Graphical abstract: Highlights: Co-existed SDS played antagonistic effect on ZnO NPs-inhibited anaerobic digestion. Co-existed SDS enhanced growth of Methanothrix, Methanosarcina, Methanobacterium. Adsorption of SDS on ZnO NPs resulted in charge reversal from positive to negative. The co-existence of SDS reduced the bio-toxic Zn 2+ release. Interaction between ZnO NPs and SDS was the mechanism of antagonistic effect. Abstract: The objective of this study was to evaluate the antagonistic effect of emerging pollutants of zinc oxide nanoparticles (ZnO NPs) and sodium dodecyl sulfate (SDS) on anaerobic digestion and explore their potential mechanism. The results indicated that at a low inhibitory concentration of ZnO NPs (1.0 mM), the practical co-inhibition was decreased by 24% and 18% in co-existence of 50 mg/L SDS and 300 mg/L SDS, respectively. More importantly, the co-existence of 300 mg/L SDS greatly enhanced methanogenesis of organics in seriously inhibited case (2.0 mM of ZnO NPs). The microbial community analysis showed that co-existed SDS enhanced the growth of Methanothrix, Methanosarcina and Methanobacterium . The antagonistic enhancement could be attributed to the net charge reversal, partially agglomeration of ZnO NPs and/or reduction of Zn 2+ release in the presence of SDS. These findings could provide useful information for evaluating the co-inhibition of SDS and ZnO NPs on biological processes.